Music therapy intervention for memory, attention, and language in children with dyslalia - López-Hernández, Edeniia (2021)
Dyslalia is a language disorder that is present in a wide percentage of children. This work proposes an intervention protocol in music therapy to improve attention, memory, and language for children with the dyslalia disorder. A confirmatory mixed-method design composed of two studies was conducted: The first included a quantitative and pre-experimental design with a sample of 20 children aged between 5 and 8 years (Mage=6.45, SD=1.23) diagnosed with dyslalia. The second study used a qualitative confirmatory methodology, where participants' parents and therapists participated. Wepman's and the initial Luria pre- and post-tests measurements were applied. The results of the pre-experiment found statistically significant improvements in verbal regulation t(19)=-5.03, p=<.001, d=.76, attention t(19)=-5.05, p=<.001, d=.76, and memory t(19)=-2.88, p=.009, d=.55. In the qualitative phase, narratives were found that affirmed the positive results of the pre-experiment. Moreover, data surrounding the benefits of the music therapy intervention protocol in the improvement of cognitive processes and the relationship with previous literature that found positive results with this type of intervention are discussed.